Students’ Perceptions of Using Google Classroom in The Process of Learning English - Rahmah, Dina Nafsirul; Graselly, Graselly; Arifin, Khoiri Aqilla; Safitri, Novita; Destari, Destari (ETDC: Indonesian Journal of Research and Educational Review, 2021)
The purpose of this article is to determine students' perceptions of the use of Google Classroom in the English learning process. This writing is made in the form of a study of documents and literatures whose understanding of knowledge is used as an analysis. Can the use of google classroom help students in learning English or not. Meanwhile, English learning takes place using Google Classroom, which can run effectively and make it easier for students to communicate and distribute assignments, provide grades, materials or conduct virtual group discussions.